Analysis of Postural Stability and Daily Energy Expenditure to Manage Tumor Patients' Functional Expectation - EROL, BÜLENT; KURTEL, HIZIR; KARADAĞ SAYGI, NAİME EVRİM (KOREAN ORTHOPAEDIC ASSOC, 2018)
Background: Advances in surgical techniques, implant technology, radiotherapy, and chemotherapy have increased the recovery chances of patients with bone sarcomas. Accordingly, patients' expectations on life quality have also increased, highlighting the importance of objective evaluation of the functional results of reconstruction. Methods: Thirteen patients with distal femoral endoprosthesis, who had been followed for an average of 2.9 years were evaluated. Postural stability, daily energy expenditure, muscle power, and range of motion were the four parameters analyzed in this study. The Musculoskeletal Tumor Society (MSTS) score and Toronto Extremity Salvage Score (TESS) were used to assess postoperative function and examine correlations with other parameters. Results: Patients had sedentary activities in 84% of their daily lives. They exhibited a slower speed in the walk across test and a higher sway velocity in the sit-to-stand test (p = 0.005). MSTS scores were significantly correlated with the daily energy expenditure and walking speed. Conclusions: Objective functional results acquired from various clinics will provide significant data to compare reconstruction techniques, rehabilitation protocols, and surgical techniques. In this way, it will be possible to satisfy the expectations of patients that increase in relation to enhanced recovery.
Keywords: Endoprostheses; Femur; Range of motion; Energy expenditure; TOTAL KNEE ARTHROPLASTY; QUALITY-OF-LIFE; PHYSICAL-ACTIVITY; HIP; PROPRIOCEPTION; OSTEOARTHRITIS; REPLACEMENT; STRENGTH; BALANCE; GAIT